Digital Media and Social Interaction in Early Childhood: A Systematic Literature Review - Besse Nirmala; Andi Agusniatih; Hesti Putri Setianingsih; Zakiyyatul Imamah; Haerul Annuar; Sirjon Sirjon (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2026)
Digital media presents both opportunities and challenges for young children’s social interaction development. Previous studies report mixed findings and often examine isolated outcomes, resulting in limited understanding of how digital media shapes early social interaction. This study addresses this gap by synthesizing recent evidence and proposing a contextual framework explaining digital media’s role in young children's social interaction. A systematic literature review was conducted using the Scopus database covering publications from 2016–2025 with keywords related to digital media, social interaction, and early childhood. From 1,067 identified articles, 25 met the inclusion criteria and were analyzed through thematic synthesis. The findings indicate that interactive and collaborative digital media use, supported by parents or teachers, enhances communication, cooperation, and social relationships. Conversely, excessive, passive, and unmediated use may reduce face-to-face interaction quality and is associated with social-emotional, language, and self-regulation challenges. This study proposes a contextual framework highlighting four influencing factors: duration of use, type of activity, technological design, and adult mediation within family and educational environments. These findings contribute theoretically by providing an integrated understanding of digital media’s role and offer practical implications for balanced and guided digital media use in early childhood settings.